Integrating drone technology in sustainable agriculture: Precision environmental monitoring and resource management - Takhumova Oksana; Pustuev Andrey; Eiryan Nikolay; Sarsadskikh Anastasia; Rykalina Olga (E3S Web of Conferences)
Current advances in data analytics further amplify the benefits, providing farmers with actionable insights to optimize plant nutrition, irrigation schedules, pest control, and harvest timing. Beyond operational gains, drone-assisted monitoring can strengthen farm resilience by identifying early indicators of soil degradation, water stress, and pest outbreaks, thus informing preventive measures. In parallel, drones can foster social and economic sustainability by lowering production costs and promoting equitable access to knowledge. Smallholder farmers, for example, can benefit from shared drone services that offset initial capital investments. Moreover, real-time, field-level data obtained via drones facilitate transparent communication among supply chain stakeholders, leading to more informed decisions and policy-making. Despite these promising outcomes, several challenges constrain the widespread integration of drones in agriculture. These include regulatory hurdles, the need for specialized training, and data privacy concerns. Additionally, drones require robust infrastructure and technical support to ensure reliability in diverse farming contexts. Addressing these issues through targeted research, policy reforms, and educational initiatives is essential to fully harness drone technology for sustainable agricultural systems. Overall, drone adoption in agriculture heralds a new era of precision farming, with the potential to revolutionize traditional practices and drive the sector towards greater environmental stewardship and socio-economic viability.